Constructing postmodernism - McHale, Brian (Routledge, 1992)
"Postmodernism is not a found object, but a manufactured artifact." Beginning from this constructivist premise, Brian McHale develops a series of readings of problematically postmodernist novelsJoyce's Ulysses; Pynchon's Gravity's Rainbow and Vineland; Eco's The Name of the Rose and Foucault's Pendulum; the novels of James McElroy and Christine Brooke-Rose, avant-garde works such as Kathy Aker's Empire of the Senseless, and works of cyberpunk science-fiction by William Gibson, Bruce Sterling, Lewis Shiner, Rudy Rucker, and others. Although mainly focused on "high" or "elite" cultural products, Constructing Postmodernism relates these products to such phenomena of postmodern popular culture as television and the cinema, paranoia and nuclear apocalypse, angelology and the cybernetic interface, and death, now as always, the true Final Frontier. McHale's previous book, Postmodernist Fiction (Routledge, 1987) seemed to propose a single, all-inclusive inventory of postmodernist poetics. This book, by contrast, proposes multiple, overlapping and intersecting inventoriesnot a construction of postmodernism, but a plurality of constructions. - Publisher description.